Le physicien devant la question de l’origine aujourd’hui - Thierry Magnin (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Examining how physics interrogates the origins of the universe, this article shows how contemporary physicists, when trying to go back to the beginnings of the world, are ultimately faced with the impossibility of retrieving the Origin. However, the resulting incompleteness must not be seen as a defeat of reason, but as an opportunity for progress : insofar as it invites the physicist to face the idea of mystery, it becomes the very condition of knowledge.